Synthesis of Spherical CdS Quantum Dots Using Cadmium Diethyldithiocarbamate as Single Source Precursor in Olive Oil Medium - Devendran, P.; Alagesan, T.; Ravindran, T.R.; Pandian, K. (Current Nanoscience, 2014)
A rapid synthesis route for the preparation of spherical cadmium sulfide (CdS) nanoparticles (NPs) was demonstrated by thermal decomposition of cadmium diethyldithiocarbamate(Cd[Ddtc]2) metal complex in the presence of a catalytic amount of hexadecylamine (HDA) using olive oil as the reaction medium. CdS nanoparticles were isolated and characterized by using HRTEM, FESEM, TGA, XRD, EDAX, PL, and Raman studies. The photocatalytic behaviour of the CdS nanoparticles was analyzed against the textile dye Congo red (CR). The degradation process follows the pseudo first order kinetics and the proposed method can be utilized for the efficient degradation of Congo red textile dye using UV light irradiation.
Keywords: CdS nanoparticles